Supporting IDPs Returning to the Territories Freed from Occupation in Term of Entrepreneurship and Income-Generating Activities - Hasanova, Aysel; Gurbanova, Aysha; Abbasov, Tural (ADA University, 2024)
This capstone project reflects the major obstacles that former IDPs in recently liberated Azerbaijani territory confront in their interest of entrepreneurial and income-generating activities. After the 44-day Patriotic War and afterwards liberation of these lands, the Azerbaijani government launched the "Great Return" programme. This involved implementing a series of reconstruction and development projects with the goal of reintegrating the former displaced people. The primary objective has been to provide job opportunities that align with the capabilities and demands of the local economy for the returning IDPs. However, there are still significant challenges to overcome. Although the "I State Programme on the Great Return to the Territories Freed from Occupation" has made progress and outlined its goals, there is still a significant gap between the number of available job opportunities and the demand in the market. This disparity particularly affects women and individuals with outdated or insufficient skills. The current employment data indicates a small proportion of IDPs involved in personal business, which reflects larger problems such as insufficient market demand in poorly inhabited regions, poor infrastructure, and a major mismatch in the necessary skills. Encouraging entrepreneurship and income-generating activities can have a significant impact on solving the challenges that arise. Entrepreneurship development can play an important role in employment generation and have a greater impact on job creation, economic, local development, flexible and adaptable sustainable employment solutions. This study will examine the fundamental causes of these problems, using survey data from ADA University to reveal the requirements for restoring basic life support. These requirements have a substantial impact on the sustainability of businesses in the region. Furthermore, the disparity in gender among returning IDPs highlights the importance of inclusiveness that specifically responds to the unique requirements of all demographic groups including women and youth. This project intends to improve the efficiency of the "Great Return" program in Azerbaijan's liberated lands by identifying the most significant underlying reasons and presenting strategic solutions. The goal is to promote sustainable development and resilience in these areas.
Keywords: Displaced persons -- Azerbaijan -- Economic conditions; Entrepreneurship -- Azerbaijan -- Development; Employment -- Azerbaijan -- Opportunities; Azerbaijan -- Social conditions -- Post-2020; Public and International Affairs